2020
DOI: 10.7554/elife.60058
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin exposure at the ring or trophozoite stage impacts Plasmodium falciparum sexual conversion differently

Abstract: Malaria transmission is dependent on the formation of gametocytes in the human blood. The sexual conversion rate, the proportion of asexual parasites that convert into gametocytes at each multiplication cycle, is variable and reflects the relative parasite investment between transmission and maintaining the infection. The impact of environmental factors such as drugs on sexual conversion rates is not well understood. We developed a robust assay using gametocyte-reporter parasite lines to accurately measure the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 75 publications
7
63
0
Order By: Relevance
“…However, how asexual cells are reprogrammed for gametocyte commitment, and the downstream post‐commitment regulation of sexual development is not well characterized. There are known examples of gametocyte stage genes such as pfsegxp, mdv1, gexp02 and pfs16 that are expressed very early on in the asexual stages, suggesting that programming for gametocytogenesis may begin early in asexual development, and disruption of this program could result in profound effects post‐commitment during sexual development (Furuya et al., 2005; Joice et al., 2014; Nixon et al., 2018; Painter et al., 2017; Portugaliza et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, how asexual cells are reprogrammed for gametocyte commitment, and the downstream post‐commitment regulation of sexual development is not well characterized. There are known examples of gametocyte stage genes such as pfsegxp, mdv1, gexp02 and pfs16 that are expressed very early on in the asexual stages, suggesting that programming for gametocytogenesis may begin early in asexual development, and disruption of this program could result in profound effects post‐commitment during sexual development (Furuya et al., 2005; Joice et al., 2014; Nixon et al., 2018; Painter et al., 2017; Portugaliza et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment with sub-curative doses of the widely used drugs chloroquine (36) and sulfadoxine/pyrimethamine ("Fansidar") (39) have been associated with increased gametocyte production in vivo. Using a transgenic reporter cell line for the quantification of sexual conversion rates (40), the Cortés laboratory recently confirmed a gametocytogenesis-inducing effect for the frontline antimalarial dihydroartemisinin (DHA) (38). In this study, short pulses of sub-curative DHA concentrations applied to trophozoites induced sexual commitment in vitro, but this effect was not observed when ring or schizont stage parasites were exposed to the drug.…”
Section: Introductionmentioning
confidence: 72%
“…For example, the different microenvironments that parasites encounter at sequestration sites, including the bone marrow and spleen, may have profound effects on drug kinetics and bioavailability. Furthermore, in recent efforts, Portugaliza and colleagues simulated the short in vivo half-life of artemisinin/DHA by exposing in vitro cultured parasites to short drug pulses and identified stage-specific effects on sexual commitment (38). While ring stage populations exposed to 3hour pulses of DHA responded with decreased SCRs, trophozoites showed elevated SCRs following drug pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent in vitro study showed that clinical isolates with K13 mutations had a higher ability to initiate gametocytogenesis and infect mosquitoes under ART drug pressure ( Witmer et al, 2020 ). Actually, exposure of trophozoites to low DHA concentrations promoted sexual conversion ( Portugaliza et al, 2020 ), providing further support for the transmission of resistant parasites after ART treatment. Moreover, ART-resistant parasites can readily infect highly diverse Anopheles mosquitoes including the primary African vector An.…”
Section: Art Resistance: the Unusual Phenotype And Underlying Mechanismsmentioning
confidence: 97%